Photovoltage Study of Graphene Oxide with Ni Nanoparticles. (2015) - Okhay, Olena; Krishna, Rahul; Titus, Elby; Andreeva, Kateryna; Savkina, Rada; Smirnov, Oleksii
Abstract: The influence of addition of Ni on photovoltage properties of graphene oxide (GO) films with reduced GO as top transparent electrode was studied. It was found that Photovoltaic response is presented in all samples at about 900-1000 nm. All spectra are different in intensity and have different position of the maximum of peak that can be explained by materials of layer and influence of substrate. Position of the maximum of peak shifts with addition of Ni, thus band gap is also changing.